1992
DOI: 10.1123/ijsb.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grip Width on Bench Press Performance

Abstract: The purpose of this study was to determine the effects of grip width, chest depth, limb lengths, and bar path on the performance of a maximal bench press. Subjects were 24 experienced male weight trainers. Bench press performance was assessed at six different grip widths (G1–G6). Repeated-measures ANOVA with Tukey post hoc comparisons revealed that bench press strength values at the two moderate grip widths (G3 and G4) were significantly greater than either the narrow or wide grip widths. First-order partial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 8 publications
6
75
2
5
Order By: Relevance
“…The three grip widths being wide defined as preferred competition grip, narrow defined as bi-acromial distance and medium in the middle of the two (Barnett et al, 1995;Lehman, 2005;Wagner et al, 1992). Only three grip widths were used to avoid fatigue that can occur when performing with more grip widths (Wagner et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three grip widths being wide defined as preferred competition grip, narrow defined as bi-acromial distance and medium in the middle of the two (Barnett et al, 1995;Lehman, 2005;Wagner et al, 1992). Only three grip widths were used to avoid fatigue that can occur when performing with more grip widths (Wagner et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Madsen and McLaughlin (1984) and Wagner, Evans, Weir, Housh, and Johnson (1992) found that one is significantly stronger with a wide grip compared to a narrow grip. However, only Wagner et al (1992) mentioned sticking region and grip width.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Brown and Wier (2001) proposed the following standardized procedures for 1RM determination based on previous recommendations (Stone and O'Bryant 1987, Kraemer and Fry 1991, Wagner et al 1992, Weir et al 1994.…”
Section: Performing 1rm Determinationmentioning
confidence: 99%
“…On the surface this finding appears to contrast with that of Wagner et al [39], particularly considering that the subjects in the study by Król et al were asked to use the uniform grip with the 81-cm spacing between palms—the widest grip allowed by the International Powerlifting Federation (IPF). As we noted in the previous paragraph, wide grip in elite powerlifters was associated with a lower sticking point location.…”
Section: Observational Researchmentioning
confidence: 78%